The Neotropical species of the genus Osorius Guérin-Meneville, 1829 with remarks to the Neotropical Osoriid complex (Coleoptera: Staphylinidae: Osoriinae). - Irmler, Ulrich (Contributions to Entomology = Beiträge zur Entomologie, 2010)
As a result of review studies on the Neotropical Osorius complex a key to the Neotropical genera of the tribe Osoriini is provided, which includes the new genus Antillosorius with 18 described species from the West Indies. New records of the two species Ouloglene barberi Notman, 1925 and Oryssoma schwarzi Notman, 1925 are given. In total, 35 species of the genus Osorius are described or redescribed. Eight new species have been found in the collections studied. These are: O. verhaaghi, O. paganus, O. venezuelanus, O. pusillus, O. ashei, O. tschirnhausi, O. guianensis, O. continentalus. The ecology of the species and zoogeographic distributions are discussed. Nomenclatural Actsbiarmatus (Darlington, 1927) (Antillosorius), comb. nov. hitherto Osorius biarmatus Darlington, 1927buscki (Notman, 1925) (Antillosorius), comb. nov. hitherto Osorius buscki Notman, 1925cautis (Darlington, 1937) (Antillosorius), comb.nov. hitherto Osorius cautis Darlington, 1937crenulifrons (Notman, 1925) (Antillosorius), comb. nov. hitherto Osorius crenulifrons Notman, 1925cubensis (Blackwelder, 1943) (Antillosorius), comb. nov. hitherto Osorius cubensis Blackwelder, 1943daemon (Darlington, 1937) (Antillosorius), comb. nov. hitherto Osorius daemon Darlington, 1937darlingtoni (Blackwelder, 1943) (Antillosorius), comb.nov. hitherto Osorius darlingtoni Blackwelder, 1943fratellus (Darlington, 1937) (Antillosorius), comb. nov. hitherto Osorius fratellus Darlington, 1937hirtilabris (Bernhauer, 1915) (Antillosorius), comb. nov. hitherto Osorius hirtilabris Bernhauer, 1915hubbardi (Notman, 1925) (Antillosorius), comb. nov. hitherto Osorius hubbardi Notman, 1925manni (Notman, 1925) (Antillosorius), comb. nov. hitherto Osorius manni Notman, 1925mediocris (Darlington, 1937) (Antillosorius), comb. nov. hitherto Osorius mediocris Darlington, 1925oriente (Blackwelder, 1943) (Antillosorius), comb. nov. hitherto Osorius oriente Blackwelder, 1943regulus (Darlington, 1937) (Antillosorius), comb. nov. hitherto Osorius regulus Darlington, 1937salutator (Darlington, 1937) (Antillosorius), comb. nov. hitherto Osorius salutator Darlington, 1937socors (Darlington, 1937) (Antillosorius), comb. nov. hitherto Osorius socors Darlington, 1937strictus (Blackwelder, 1943) (Antillosorius), comb. nov. hitherto Osorius strictus Blackwelder,1943turquinus (Blackwelder, 1943) (Antillosorius), comb. nov. hitherto Osorius turquinus Blackwelder,1943ashei Irmler, 2010 (Osorius), spec. nov.asymetricus Fauvel, 1901 (Osorius), syn. nov. of Osorius brasiliensis Guérin, 1829continentalus Irmler, 2010 (Osorius), spec. nov.guianensis Irmler, 2010 (Osorius), spec. nov.laevigatus Sharp, 1887 (Osorius), syn. nov. of Osorius dubius Sharp, 1887latimargo Bernhauer, 1908 (Osorius), syn. nov. of Osorius nitens Sharp, 1876paganus Irmler, 2010 (Osorius), spec. nov.pusillus Irmler, 2010 (Osorius), spec. nov.simplex Sharp, 1876 (Osorius), syn. nov. of Osorius nitens Sharp, 1876tschirnhausi Irmler, 2010 (Osorius), spec. nov.venezuelanus Irmler, 2010 (Osorius), spec. nov.verhaaghi Irmler, 2010 (Osorius), spec. nov.Antillosorius Irmler, 2010 (Staphylinidae), gen. nov.